2013
DOI: 10.1159/000353549
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mediastinal Dissection for Papillary Thyroid Carcinoma: Approaches and Outcomes

Abstract: Background: Superior mediastinal surgery for thyroid carcinoma is not a standardized procedure like the neck dissection. The objective of this study was to evaluate the effectiveness of superior mediastinal dissection for mediastinal metastasis of papillary thyroid carcinoma (PTC). Methods: We conducted a retrospective review of 119 patients who underwent superior mediastinal dissection for the treatment of PTC. The postoperative characteristics and follow-up data were analyzed. Cox regression was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Surgeons prefer to avoid SMLND because of the incidence of surgical morbidity related to the procedure, stemming from major vessel injury, hypoparathyroidism, recurrent laryngeal nerve injury, pneumothorax, and pleural effusion[ 21 ]. However, a previous study has already reported the safety of SMLND without life-threatening complications[ 22 ]. Moreover, transcervical SMLND is a useful and safe surgical approach to access the superior mediastinum between the sternal notch and the innominate vasculature[ 1 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons prefer to avoid SMLND because of the incidence of surgical morbidity related to the procedure, stemming from major vessel injury, hypoparathyroidism, recurrent laryngeal nerve injury, pneumothorax, and pleural effusion[ 21 ]. However, a previous study has already reported the safety of SMLND without life-threatening complications[ 22 ]. Moreover, transcervical SMLND is a useful and safe surgical approach to access the superior mediastinum between the sternal notch and the innominate vasculature[ 1 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study has already reported the safety of SMLND without life-threatening complications[ 22 ]. Moreover, transcervical SMLND is a useful and safe surgical approach to access the superior mediastinum between the sternal notch and the innominate vasculature[ 1 , 22 ]. However, it is worth noting that one study showed a high rate of transient hypoparathyroidism (70%) and of permanent hyperparathyroidism (50%)[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many predictive factors for MLNM were discussed in previous studies [ 6 , 7 , 10 , 11 , 14 16 , 18 , 20 , 22 , 23 ], but most of them are still controversial ( Table 5 ). Nevertheless, it mainly came to an accordant conclusion that the patients with bilateral cervical metastasis [ 10 , 15 , 18 , 22 , 23 ] or with distant metastasis [ 10 , 11 , 15 , 18 ] and the patients who underwent reoperation [ 6 , 18 , 20 ] had increased risk of MLNM. And the predictive factors discussed in each study were shown in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…There are totally five studies [ 7 , 10 , 13 , 16 , 19 ] revealing the prognosis of the patients with MLNM. Liu et al [ 10 ] demonstrated that the incidences of death, recurrence, and distant metastasis were 12.6%, 14.3%, and 16.8%, respectively, based on 119 PTC cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation